Did the Flores backarc thrust rupture offshore during the 2018 Lombok earthquake sequence in Indonesia?. Issue 2 (25th February 2020) - Yang, Xiaodong; Singh, Satish C; Tripathi, Anand
SUMMARY: The Flores thrust forms the west segment (∼450 km) of a very active, ∼E–W striking, ∼800-km-long backarc thrust along the east Sunda Arc. In 2018, a deadly earthquake sequence composed of ~110 M 4+ events rattled the Indonesian island of Lombok near the Flores thrust and caused tremendous damage on the island, however what is the nature of rupturing during this earthquake sequence remains unknown. Here, using a total of 2120 km of high-resolution seismic profiles covering ∼300 km of the Flores thrust off Bali, Lombok and Sumbawa, in addition to earthquake data and InSAR measurements, we investigated the active thrusting during this earthquake sequence. Our seismic interpretation and structural mapping show that offshore north of Lombok and Bali, the remarkable Flores thrust is essentially blind, deforming the seabed by folds, not faults. The Lombok earthquakes were all shallow thrust events with depth <40 km and occurred within ∼35 km north of the Rinjani volcano beneath the Lombok Island and its northern extremity. The InSAR measurements suggested that the most of the crustal deformation caused by these earthquakes occurred the north the and northeast of the island. The maximum vertical deformation was ∼36 cm near the northwest margin of the island, caused by the 5th August M w 6.9 event. These observations combined with the presence of blind thrusts off Lombok suggest that the offshore portion of Flores thrust did not rupture during the 2018 Lombok earthquake sequence; the most coseismic slip must have occurred along a deep-rooted, north-verging basal fault and a range of imbricate thrusts beneath the north of the island, not along the buried thrusts offshore. Despite being blind off Lombok and Bali, the Flores thrust can still pose tsunami threats to the adjacent population centres by rupturing the seafloor during future large earthquakes ( M  > 7) that occur directly on the offshore blind thrusts, not beneath the island like the Lombok sequence. The proximity of the Rinjani volcano and thrust earthquakes suggests a possible role of volcanic activity (e.g. magmatic fluids and gas migration, stress change induced by pressurized magma chamber) in inducing the Lombok earthquakes.